Classroom Translation of Tabib's Poem: A Practical Model for Analysis and Evaluation of Poetry Discourse Translation - taheri, aysu (International Journal of Language and Literary Studies, 2021)
Poetry Translation is a high-quality open access translation of classical texts by famous poets, the characteristics of poetry can be based on sound, syntax, structure or pragmatics. In addition to text transformation, poetic translation is concerned with the perception, discourse and action of and between people and textual agents in a material and social context. A public poetry translation project generally aims to feature one or more poets. Poetry translators are interested in interpreting the meaning layers of the source poem, they rely on reliability to judge this and produce a poem in the target language that is readable and pleasing to the literary text. They are responsible for making their writing easy to understand. The reader is also responsible for understanding the translator's translation. The possible solutions to these problems are collaboration between authors and translators. This article highlights the challenges associated with translating poetry. Although poetry makes up only a small percentage of the world's translation output, case studies and examples from poetry have dominated theoretical construction in translation studies to the detriment of genres translated more often.